Determining Aspergillus fumigatus transcription factor expression and function during invasion of the mammalian lung. - Hong Liu; Wenjie Xu; Vincent M Bruno; Quynh T Phan; Norma V Solis; Carol A Woolford; Rachel L Ehrlich; Amol C Shetty; Carrie McCraken; Jianfeng Lin; Michael J Bromley; Aaron P Mitchell; et al. (PLoS Pathogens)
To gain a better understanding of the transcriptional response of Aspergillus fumigatus during invasive pulmonary infection, we used a NanoString nCounter to assess the transcript levels of 467 A. fumigatus genes during growth in the lungs of immunosuppressed mice. These genes included ones known to respond to diverse environmental conditions and those encoding most transcription factors in the A. fumigatus genome. We found that invasive growth in vivo induces a unique transcriptional profile as the organism responds to nutrient limitation and attack by host phagocytes. This in vivo transcriptional response is largely mimicked by in vitro growth in Aspergillus minimal medium that is deficient in nitrogen, iron, and/or zinc. From the transcriptional profiling data, we selected 9 transcription factor genes that were either highly expressed or strongly up-regulated during in vivo growth. Deletion mutants were constructed for each of these genes and assessed for virulence in mice. Two transcription factor genes were found to be required for maximal virulence. One was rlmA, which is required for the organism to achieve maximal fungal burden in the lung. The other was sltA, which regulates of the expression of multiple secondary metabolite gene clusters and mycotoxin genes independently of laeA. Using deletion and overexpression mutants, we determined that the attenuated virulence of the ΔsltA mutant is due in part to decreased expression aspf1, which specifies a ribotoxin, but is not mediated by reduced expression of the fumigaclavine gene cluster or the fumagillin-pseruotin supercluster. Thus, in vivo transcriptional profiling focused on transcription factors genes provides a facile approach to identifying novel virulence regulators.